The Maintaining Musculoskeletal Health (MAmMOTH) Study: Protocol for a randomised trial of cognitive behavioural therapy versus usual care for the prevention of chronic widespread pain - Macfarlane, Gary J. (BMC Musculoskelet Disord, 2016)
BACKGROUND: Cognitive behavioural therapy (CBT) has been shown to improve outcomes for patients with fibromyalgia, and its cardinal feature chronic widespread pain (CWP). Prediction models have now been developed which identify groups who are at high-risk of developing CWP. It would be beneficial to be able to prevent the development of CWP in these people because of the high cost of symptoms and because once established they are difficult to manage. We will test the hypothesis that among patients who are identified as at high-risk, a short course of telephone-delivered CBT (tCBT) reduces the onset of CWP. We will further determine the cost-effectiveness of such a preventative intervention. METHODS: The study will be a two-arm randomised trial testing a course of tCBT against usual care for prevention of CWP. Eligible participants will be identified from a screening questionnaire sent to patients registered at general practices within three Scottish health boards. Those returning questionnaires indicating they have visited their doctor for regional pain in the last 6 months, and who have two of, sleep problems, maladaptive behaviour response to illness, or high number of somatic symptoms, will be invited to participate. After giving consent, participants will be randomly allocated to either tCBT or usual care. We aim to recruit 473 participants to each treatment arm. Participants in the tCBT group will have an initial assessment with a CBT therapist by telephone, then 6 weekly sessions, and booster sessions 3 and 6 months after treatment start. Those in the usual care group will receive no additional intervention. Follow-up questionnaires measuring the same items as the screening survey questionnaire will be sent 3, 12 and 24 months after start of treatment. The main outcome will be CWP at the 12 month questionnaire. DISCUSSION: This will be the first trial of an intervention aimed at preventing fibromyalgia or CWP. The results of the study will help to inform future treatments for the prevention of chronic pain, and aetiological models of its development. TRIAL REGISTRATION: ClinicalTrials.gov ID: NCT02668003URL: Please check that the following URLs are working. If not, please provide alternatives: NCT02668003Alternative is: https://www.clinicaltrials.gov/ct2/show/NCT02668003>. Date registered: 28-Jan-2016.